Experimental analysis of track-ground vibrations on a stretch of the Portuguese railway network. Issue 90 (November 2016) - dos Santos, N. Correia; Colaço, A.; Costa, P. Alves; Calçada, R.
Abstract: This paper presents a comprehensive experimental campaign developed on a stretch of the Portuguese railway network. The experimental work includes three fundamental and complementary components: the characterization of the ground, the characterization of the track and the measurement of the vibrations generated by railway traffic. The characterization of the ground was performed using a combination of conventional and geophysical tests (cross-hole and SASW). The mechanical characterization of the track was performed through receptance tests and the rail unevenness profile was accurately measured. The vibrations due to the passage of more than 20 trains were measured. First, a selection of the results is presented and analysed in detail; later, the variability of the responses is briefly discussed. The presented data may be used by other researchers (e.g. in the validation of their prediction models), since it can be downloaded fromwww.fe.up.pt/~csf/DataCarregado.zip . Highlights: A comprehensive experimental campaign is presented. The dynamic behaviour of the track is analysed by mean of receptance tests. The vibrations induced by the passage of more than 20 trains were measured. The dispersion of the results is analysed and discussed. The main results of the experimental campaign are available for download.